Establishing C. elegans models of human congenital myasthenic syndromes - Bergé, Ignacio (2013)
The free-living nematode Caenorhabditis elegans is a model for the study of human neurological diseases and drug testing. In humans, gain-of-function mutations in muscle nicotinic receptor (AChR) subunits lead to slow-channel congenital myasthenic syndromes. We here explored if homologous mutations in C. elegans subunits mimic the molecular and functional changes observed in patients. In the essential UNC-38 and UNC-29 subunits of the levamisole-sensitive AChR (L-AChR) we mutated residues at position 9’ of M2, which forms the gate of the channel, and position 12’, which mimics a mutation found in a patient. We generated transgenic worms expressing the mutant AChRs in muscle using both wild-type and null-mutant strains as backgrounds. Electrophysiological studies show a dramatic increase (14-fold) in the open duration of L-AChR channels, and a decrease in the desensitization rate of macroscopic currents elicited by ACh, similarly to the changes detected in human mutant AChRs. Unexpectedly, no significant changes in locomotion and levamisole-sensitivity of transgenic worms occur. Overall, our results show that mutant subunits are incorporated into functional L-AChRs and lead to kinetic changes similar to those observed in vertebrate AChRs, thus revealing a high degree of conservation of functional roles of amino acids between C. elegans and human AChRs. These results open doors for establishing C. elegans models for human myasthenic syndromes.